Pendidikan Pesantren Dalam Perspektif Pendidikan Nasional - Setiawan, Agus; Norman, Efrita (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2020)
This research is conducted to analyse national education perception towards Islamic education. In the Constitution of Republic of Indonesia 1945 article 3 section 3, there was at least two purposes of national education, which are increasing faith, piety, and moral. Based on that points, either directly or indirectly this section is addressed to religious-based education institutions, which one of them is Islam boarding school. In Constitution of Republic of Indonesia number 18 2019 related to boarding school, in article 15 stated that